2013
DOI: 10.29173/cais598
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in Public and Academic North American Libraries, in Words and Deeds

Abstract: Being innovative is a popular but ambiguous maxim in LIS. To elucidate how institutions use, and what they mean by the concept, we examine white literature and survey website features of 160 libraries across US and Canada. We identify patterns in the language and ethos of modern innovative librarianship.Être novateur est une maxime populaire bien qu’ambigüe en science de l’information. Pour mieux comprendre comment les institutions l’utilisent et quelle est la signification du concept, nous avons analysé les d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Rogers' diffusion of innovations theory is described as the most appropriate model for investigating the adoption of technology in higher educational environments (Sahin, 2006), and as being applicable to innovation in library and information science (Rubin et al, 2011;Martin and Quan-Haase, 2011). It is therefore from Rogers' (2003) theory that the three terms relevant to this research paper are derived, namely diffusion, adoption and implementation.…”
Section: Methodsmentioning
confidence: 99%
“…Rogers' diffusion of innovations theory is described as the most appropriate model for investigating the adoption of technology in higher educational environments (Sahin, 2006), and as being applicable to innovation in library and information science (Rubin et al, 2011;Martin and Quan-Haase, 2011). It is therefore from Rogers' (2003) theory that the three terms relevant to this research paper are derived, namely diffusion, adoption and implementation.…”
Section: Methodsmentioning
confidence: 99%
“…Rubin et al (2011) respond to Knab’s (2010) appeal to define the term innovation for librarianship by reviewing the literature on innovation and the description of library services on publicly accessible websites of 160 public and academic libraries in North America. Their secondary research identified the following 10 areas of innovation in libraries: technology, service, culture, vague, character, use, program, facility, resource, and partnership.…”
Section: Types Of Innovations In Organizationsmentioning
confidence: 99%
“…service and program, facility and resource, etc.). Secondly, Rubin et al (2011) acknowledge that their study does not cover “backend” innovations such as staff reorganizations, which are typically not broadcast on the websites of the libraries studied. In contrast, our study proposes mutually exclusive categories of innovations based on the responses collected from library administrators.…”
Section: Types Of Innovations In Organizationsmentioning
confidence: 99%
“…This lack of precision is troubling. Rubin, Gavin and Kamal (2011) conclude that the absence of definitional specificity suggests that librarians use the term as a "makeshift remedy" in the face of social and economic change for which they lack solutions.…”
Section: Innovation As Solutionmentioning
confidence: 97%
“…Though frequently discussed in the literature of academic libraries (Clayton, 1997;Deiss, 2004;Musmann, 1982;Reynolds & Whitlatch, 1985;Rubin, Gavin, & Kamal, 2011;Willard, 1991), innovation remains an ambiguous and shallowly defined concept. Typically, innovation refers to a service, product or activity that is new to a specific context (Clayton, 1997), a usage derived from organization studies (Aiken & Hage, 1971).…”
Section: Innovation As Solutionmentioning
confidence: 99%